PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA PEGAWAI DI MASA PANDEMI COVID-19 - M Yusuf Hari Nugroho; Yulianto Yulianto; Simon Sumanjoyo Hutagalung (P3M STISIPOL Dharma Wacana Metro, 2023)
This research is motivated by obsevational data that shows the low work motivation of the employees of the Kampung Sawah Community Health Center in Bandar Lampung. Thus, this research is intended to measure the effect of leadership model partially and simultaneously on the work motivation of the employees of the Kampung Sawah Community Health Center in Bandar Lampung. This research was conducted on all 60 employees of the Kampung Sawah Community Health Center in Bandar Lampung, using explanatory research and a quantitative approach. The results of this study indicate that partially the Directive Leadership, Supportive Leadership, and Achievement Oriented Leadership have no significant effect on the Work Motivation variable. While the Participative Leadership has a significant effect on the employees Work Motivation. However, simultaneously there is a significant influence between Directive Leadership, Supportive Leadership, Participative Leadership and Achievement Oriented Leadership on Work Motivation of Kampung Sawah Community Health Center Employees in Bandar Lampung. Thus, from this study the results showed that the Leadership Model variable had an influence of 53.8% on the Work Motivation variable.